Knowledge of agricultural extension Workers in the field of integral Weed control in the region of AlGabal Alakhtar - Awad, Abdel Aziz A.; Alzobaidy, Dakhel Hussein (Al-Mukhtar Journal of Sciences, 2009)
This research aimed to identify the knowledge of levels of agricultural extension workers in the field of weed control and the relationship of the knowledge level by their professional characteristics ,and training topics according to training need. Data were collected from a sample accounted ( 80 ) extension workers through questionnaires and personal interview . Frequency tables, percentages, average, and K2 were used in data analysis of this research. The research members were of low knowledge level in a percentage of 75%. A significant relationship existed at 0.01 level between the educational qualification and the period of work in extension. Also there was a significant relationship at 0.05 level between the number of training period in the field of weed control and the knowledge level. The results showed that there were 7 topics through which the researched showed workers need to be trained.